2008
DOI: 10.1097/01.ncn.0000304800.93003.b4
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Nursing Clinical Decision Support System to Promote Guideline Adherence

Abstract: This article describes the development and implementation of a nursing clinical decision support system that prompts nurses to place mechanically ventilated patients in a semirecumbent position in the absence of contraindications. A literature review is provided regarding (1) ventilator-associated pneumonia and recommendations from expert panels to maintain mechanically ventilated patients in a semirecumbent position (unless contraindicated) and (2) clinical decision support systems. Use of clinical decision s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…However, physicians identified a number of barriers that were likely to reduce CDS utilization in clinical practice—the most common barrier being the increasing cognitive burden on providers due to EHR complexity and limited time during clinical encounters. These findings are supported by previous studies that examined barriers to CDS implementation [ 9 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, physicians identified a number of barriers that were likely to reduce CDS utilization in clinical practice—the most common barrier being the increasing cognitive burden on providers due to EHR complexity and limited time during clinical encounters. These findings are supported by previous studies that examined barriers to CDS implementation [ 9 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…There are no systematic reviews on the effect of computer reminders on nursing performance or patient outcomes; there are however systematic reviews on CDSS which have shown that CDSS effectiveness in nursing practice is still inconsistent and that further studies are needed in order to identify in which contexts they are most effective [ 16 , 17 ]. Studies in recent years of CDSS have shown improvement in nursing recording [ 18 ] and patient outcomes [ 19 ], but single studies of computer reminders have shown effect on nurses’ adherence to CPGs [ 20 ] and decreased omissions in nursing care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional information on the development and implementation of the nursing CDSS used in this study is reported elsewhere. 28 …”
Section: Study Design and Settingmentioning
confidence: 99%